Village Fund Aid Program Support System In Kel. Kandang Limun Bengkulu City Using The Weighted Product (WP) Method - Syahputra, Ferry Andrean; Darmi, Yulia; Pharizal, Pharizal; Gunawan, Gunawan (SINTA Journal (Science, Technology, and Agricultural), 2024)
The problems that occur in the provision of village funding assistance programs in Kandang Limun Subdistrict are mostly slow assessment processes and inaccurate delivery of assistance to recipients (the community). Data collection was carried out in the sub-district by means of observation, interviews and literature study. The criteria data obtained according to interviews with sub-district staff are husband's income, number of dependents, wife's income and citizenship status. The Weighted Product (WP) method can carry out rankings based on predetermined criteria and filled in with the weight values for each criterion. Determining recipients of village fund program assistance in the Kendang Limun sub-district is carried out based on ranking values using the Weighted Product (WP) method, namely based on serial numbers. Where the priority for receiving assistance starts from serial number 1 in the ranking.